Administration of a Polyphenol-Enriched Feed to Farmed Sea Bass (Dicentrarchus labrax L.) Modulates Intestinal and Spleen Immune Responses. (8th December 2015) - Magrone, Thea; Fontana, Sergio; Laforgia, Flavia; Dragone, Teresa; Jirillo, Emilio; Passantino, Letizia
Abstract : Farmed fish are exposed to a continuous antigenic pressure by microbial and environmental agents, which may lead to a condition of chronic inflammation. In view of the notion that polyphenols, largely contained in fruits and vegetables, are endowed with antioxidant and anti-inflammatory activities, farmed sea bass ( Dicentrarchus labrax L.) have been administered with red grape polyphenol-enriched feed. Polyphenols were extracted from the seeds of Canosina Nero di Troia Vitis vinifera and mixed with conventional feed at two different concentrations (100 and 200 mg/kg, resp.). Fish samples collected at days 223 and 273, respectively, were evaluated for intestinal and spleen cytokine release as well as for spleen macrophage (MØ) and melanomacrophage center (MMC) areas and distribution. Data will show that in treated fish decrease of intestinal interleukin- (IL-) 1 β and IL-6 and increase of splenic interferon- (IFN-) γ occur. On the other hand, in the spleen reduction of MØ number seems to parallel increase in MMCs. Collectively, these data suggest that polyphenol-administered sea bass generate lower levels of intestinal proinflammatory cytokines, while producing larger amounts of spleen IFN- γ, as an expression of a robust and protective adaptive immune response. Increase of MMCs corroborates the evidence for a protective spleen response induced by feed enriched with polyphenols.